Bis(2,2′-bipyridyl dioxide-κ(2) N,N′)bis(tricyanomethanido)cobalt(II) dihydrate - Qiu, Li-Juan (International Union of Crystallography, 2010)
In the title compound, [Co(C(4)N(3))(2)(C(10)H(8)N(2)O(2))]·2H(2)O, a novel tricyanomethanide complex, the Co(II) atom is located on an inversion center and has a distorted octahedral coordination with two 2,2′-bipyridyl dioxide (dpdo) molecules and two trans tricyanomethanide (tcm) anions. The equatorial plane is formed by the four O atoms of the two chelating dpdo ligands, with one N atom of each of the two tcm ligands occupying an apical position. There is a disordered solvent water molecule in the asymmetric unit (occupancy ratio 0.63:0.37). These water molecules result in the formation of O—H⋯O and O—H⋯N hydrogen bonds, building a layer parallel to (100). The layers are linked by C—H⋯N hydrogen-bonding interactions, leading to a three-dimensional network.